Scour effects on bearing capacity of composite bucket foundation for offshore wind turbines. Issue 2 (7th February 2020) - Zhao, Xing; Zhang, Puyang; Lv, Yajun; Ding, Hongyan
Abstract: Composite bucket foundation (CBF) is a wide-shallow foundation for offshore wind turbines, which can be transported and installed with the turbine as one unit at a one-step operation. Compared with deep pile foundations, its structural stability is more sensitive to the scouring by waves and currents. In this paper, a three-dimensional finite element model with CBF and surrounding soil is established to estimate the failure mode at different given soil scour conditions. The loading on CBF for offshore wind turbines is characterized by relatively small vertical loading V, larger horizontal loading H, and bending moment M, and the effect of erosion on bearing capacity of CBF is determined by using the fixed displacement ratio method. In addition, the failure envelopes of the CBF applied in H – M and V – H – M loading modes are obtained. Results indicate that the bearing capacity of CBF under horizontal loading and bending moment will be significantly reduced by the decrease in the embedded depth of CBF due to the scouring depth and extent, as well as the H – M, and V – H – M failure envelopes. The structural stability safety factor of CBF under different scouring conditions can be obtained through the three-dimensional envelope surface with respect to scouring depth and extent.